Challenges in Teaching English in Indonesian Rural Schools: Issues and Solution - Mariyam, Siti; Pratiwi, Dwiyani; Meraj, Mohammed (Universitas Pendidikan Mandalika, 2025)
The disparity in educational quality between urban and rural areas in Indonesia significantly impacts English language learning in remote schools. This study explores the key challenges English teachers face in rural settings and the pedagogical strategies they employ to overcome them. Using a qualitative research design with semi-structured interviews, five English teachers from various rural schools in Nusa Tenggara Barat were interviewed. Thematic analysis revealed several core challenges, including inadequate infrastructure, limited internet connectivity, a shortage of qualified teachers, and insufficient supervision and motivation. Despite these issues, teachers have adopted strategies such as understanding local community needs, applying inclusive teaching methods, leveraging limited technology, and engaging in professional development. These findings highlight the urgent need for targeted policy intervention to improve English instruction in rural areas. The study provides valuable insights for educators, policymakers, and researchers interested in equitable education reform. Therefore, the researcher believed that this study is beneficial for future researchers and readers, particularly in educational contexts.